RESILIENCE OF USING CULTURE: Phenomenological Study of 'Street Singers' in Banyuwangi - Rochsun; Mukarom; Jasuli; Nurcholis Sunuyeko (Journey: Journal of English Language and Pedagogy, 2022)
This study aims to portray the resilience of Using culture through a phenomenological study of 'street singers' (pengamen) in Banyuwangi. The street singers of Banyuwangi also colore the richness of Using culture and appear to present Using ethnic songs in expressing their artistic activities. The influence of global culture is increasingly difficult to be blocked [1] [2], meanwhile geographically, the location of the cultural existence is precisely at the crossroads of two major cultures, namely Javanese and Balinese cultures [3]. Qualitative research through phenomenological studies was conducted through in-depth interviews with cultural actors (street singers) and the Using supporting community of Banyuwangi. The data is then analyzed through the sequence stages: (1) transcribing the recorded interview results to written form, (2) bracketing (epoche), (3) taking an inventory of important statements (horizonalization), (4) formulating into the meaning (cluster of meaning) and (5) performing the descriptions of the essence. The results of this study cover two important things. First, Using culture can survive because of the aclak (active), bingkak (creative) and ladak (innovative) spirits of Using cultural actors. Second, the acceptance of the Banyuwangi community in general for the artistic expression of Using songs due to the consequences of the defense (uri-uri) spirit of the community. This study concludes that the preservation of Using culture is based on the internal spirit (active, creative, innovative) of cultural actors and external spirit, namely the process of preservation (uri-uri).